EKUITAS MEREK DAN PENGARUHNYA TERHADAP KEPUASAN PENGGUNA SMARTPHONE DI KOTA AMBON - Tanihattu, Maudy Marla (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
This study aimed to analyze the effect of brand equity consists ofbrand awareness, brand association, perceived brand quality and brandloyalty to consumer satisfaction using smartphones in Ambon, and test thebrand equity variables that have the most dominant effect.Data is collectedusing a questionnaire distributed to 150 respondents accidental. The datacollected was processed using SPSS 19.0 and analyzed using multipleregressions.The results show the variables that brand equity consists of brandawareness, brand association, the impression of the quality of the brand, andbrand loyalty has a significant influence either partially or simultaneously tothe satisfaction of the consumer smartphone users in the city of Ambon.Furthermore, the variable perceived quality of the brand is a variable thathas a more dominant influence on consumer satisfaction smartphone users inthe city of Ambon. Thus the first hypothesis proposed in this study isacceptable, while the second hypothesis is rejected.Keywords: brand equity, brand awareness, brand association, perceived ofbrand quality, brand loyalty, customer satisfaction